2019
DOI: 10.2147/ott.s197682
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cell-free miR-17-5p as a diagnostic biomarker for gastric cancer inhibits dendritic cell maturation</p>

Abstract: Purpose Gastric cancer (GC) patients display aberrant miRNA expression and defective dendritic cell function. However, the role of cancer cell-derived oncomiR in GC detection and dendritic cell (DC) maturation remains largely elusive. Methods Candidate miRNAs were selected by deep sequencing (8 GC plasma samples vs 8 control plasma samples; 8 GC tissues vs 8 adjacent normal gastric tissues) and confirmed by PCR with 164 plasma samples and 72 formalin-fixed paraffin-embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…MicroRNA‐27a‐3p can regulate tumor cell invasion and migration through dual specificity protein phosphatase 16 . MicroRNA‐17‐5p can exert an antitumor immune response by inhibiting dendritic cells . MicroRNA‐20b‐5p‐mimic can inhibit tumorigenicity of HCT‐116 cells in Balb/c mice .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA‐27a‐3p can regulate tumor cell invasion and migration through dual specificity protein phosphatase 16 . MicroRNA‐17‐5p can exert an antitumor immune response by inhibiting dendritic cells . MicroRNA‐20b‐5p‐mimic can inhibit tumorigenicity of HCT‐116 cells in Balb/c mice .…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that periodontitis might be affected by miR-125b-5p. Similarly, miR-17-5p and miR-21-5p were reported to play a part in periodontitis and migration of DCs and were predicted to get involved in NAFLD (Du et al, 2016;Kim et al, 2017;Reis et al, 2018;Cui et al, 2019;Zhang et al, 2020;Lin et al, 2022). Although these miRNAs have not been verified in the microenvironment of comorbidity with periodontitis and NAFLD, they also provide important therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified miRNAs within EVs with essential roles in DC function, a subset of these miRNAs target genes found to be down-regulated in DCs cultivated in the presence of EVs (Table 3 ). In fact, miRNAs have been shown to contribute to the inibition of immune responses when carried by EVs, with effects on monocyte differentiation into macrophages 36 , production of inflammatory cytokines and co-stimulatory molecules by DCs 38 , 39 , antigen processing and presentation 41 , MHC II molecules expression 29 , 49 , DC maturation 44 , 52 , migration 47 , and increased DC death 51 . Additionally, these miRNAs could potentially cooperate to regulate genes involved in these processes since different miRNAs carried by EVs were shown to regulate the same genes: miR-17-5p, miR-21, miR-24 and miR-181 target TNF-a 41 , 44 , 45 , miR-17-5p and miR-24 target IL-12 41 , 44 , and miR-155 and miR-181 regulate IL-1 42 , 60 .…”
Section: Discussionmentioning
confidence: 99%